First‐trimester combined screening for trisomy 21 in women with renal disease. (2nd February 2015) - Valentin, Morgane; Muller, Françoise; Beaujard, Marie Paule; Dreux, Sophie; Czerkiewicz, Isabelle; Meyer, Valérie; Leruez, Marianne; Ville, Yves; Salomon, Laurent J.
Abstract Objective To evaluate the results of first‐trimester combined screening for Down syndrome in women with chronic renal disease. Method Fifty‐five pregnant women with renal disease were compared with 110 patients matched for maternal age, maternal weight, smoking status, and gestational age. Maternal renal function was assayed at the time of the combined screening, and renal insufficiency was defined by serum creatinine >90 µmol/L and renal clearance <80 mL/min. We defined three groups: kidney disease and normal renal function (group 1), kidney disease and renal insufficiency (group 2), and a control group (group 3). The values of nuchal translucency, pregnancy‐associated plasma protein A, human β‐chorionic gonadotrophin (hCGβ), and false‐positive rates for Down syndrome screening were compared. Results There were 39 (71%) and 16 (29%) cases in groups 1 and 2, respectively. Nuchal translucency and multiple of the median (MoM) pregnancy‐associated plasma protein A were similar in the three groups. However, MoM hCGβ levels were higher in group 2 than in groups 1 and 3 (5.37 vs 1.1 vs 0.98 MoM, p = 0.0001). The resulting screen‐positive rate was also higher in group 2 than in groups 1 and 3 (43.7% vs 10.2% vs 5.5%, p = 0.0001). Conclusion Trisomy 21 first‐trimester screening using hCGβ is not suitable in the case of maternal renal failure. © 2014 John Wiley & Sons, Ltd.